The ISLAMIC FINANCIAL LITERACY: A THEORETICAL VIEW - Umi Widyastuti (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
This study aims to define a conceptual view of the Islamic financial literacy. This paper elaborates some scholars, which have explored financial literacy based on various dimensions to develop the concept of Islamic financial literacy. Based on previous literature, this study evolved the definition of Islamic financial literacy as the ability of individual to understand knowledge about the Islamic principles and Islamic contracts in financial decisions making to achieve one's financial well-being.